Effects of a Bacopa monnieri extract (Bacognize®) on stress, fatigue, quality of life and sleep in adults with self-reported poor sleep: A randomised, double-blind, placebo-controlled study. (October 2021) - Lopresti, Adrian L.; Smith, Stephen J; Ali, Sinan; Metse, Alexandra P.; Kalns, John; Drummond, Peter D.
Graphical abstract: Highlights: Bacopa monnieri supplementation did not improve sleep patterns more than the placebo. Bacopa monnieri increased self-reported emotional wellbeing and general health. Salivary immunoglobulin A and α-amylase reduced after Bacopa monnieri supplementation. Future trials investigating the mood-enhancing effects of Bacopa monnieri will be important. Abstract: In this 28-day, randomised, double-blind, placebo-controlled trial, 100 adults with self-reported poor sleep received either a placebo or a standardised Bacopa monnieri extract (150 mg twice daily). Outcome measures included the Bergen Insomnia Scale (primary outcome measure), Functional Outcomes of Sleep Questionnaire, Pittsburgh Sleep Diary, Short Form-36 Health Survey, and the Depression, Anxiety, and Stress Scale. Changes in salivary concentrations of cortisol, dehydroepiandrosterone sulfate, immunoglobulin A (sIgA), α-amylase (sAA), C-reactive protein, melatonin, and the fatigue biomarker index were also assessed. Based on the Bergen Insomnia Scale, Bacopa monnieri did not improve sleep patterns more than the placebo; however, it was associated with greater improvements in emotional wellbeing, general health, and pain-related symptoms. Bacopa monnieri was also associated with greater reductions in sIgA and sAA compared to the placebo. Future clinical trials using varying doses, treatment periods, and objective outcome measures will be important to validate these findings.